2011
DOI: 10.1159/000322449
|View full text |Cite
|
Sign up to set email alerts
|

Prenatal Complex Rhythmic Music Sound Stimulation Facilitates Postnatal Spatial Learning but Transiently Impairs Memory in the Domestic Chick

Abstract: Early experience has a profound influence on brain development, and the modulation of prenatal perceptual learning by external environmental stimuli has been shown in birds, rodents and mammals. In the present study, the effect of prenatal complex rhythmic music sound stimulation on postnatal spatial learning, memory and isolation stress was observed. Auditory stimulation with either music or species-specific sounds or no stimulation (control) was provided to separate sets of fertilized eggs from day 10 of inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(25 citation statements)
references
References 68 publications
0
25
0
Order By: Relevance
“…In a similar way, auditory stimulation exerts a profound effect on the development of auditory areas as well as hippocampus of chicks (20, 52). Earlier studies from our laboratory have shown improvement in spatial orientation [18] and learning [18], [22] of neonatal chicks after exposure to prenatal species-specific as well as non species-specific sound (music) stimulation at 65 dB, suggesting an early maturation of neural connectivity. In the present study, the beneficial effects of music on learning and memory were seen even with higher sound pressure level of 110 dB.…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…In a similar way, auditory stimulation exerts a profound effect on the development of auditory areas as well as hippocampus of chicks (20, 52). Earlier studies from our laboratory have shown improvement in spatial orientation [18] and learning [18], [22] of neonatal chicks after exposure to prenatal species-specific as well as non species-specific sound (music) stimulation at 65 dB, suggesting an early maturation of neural connectivity. In the present study, the beneficial effects of music on learning and memory were seen even with higher sound pressure level of 110 dB.…”
Section: Discussionmentioning
confidence: 81%
“…The facilitation of learning was observed even at 24 hour post hatch with no further improvement in successive trials following the same sound enrichment protocol suggesting an early maturation of synaptic connectivity following prenatal sound stimulation. Significant memory retention at 72 and 120 hour post hatch with a transient impairment at 24 hour post hatch following prenatal music stimulation was observed [22]. The avian hippocampus is involved in spatial learning as well as in memory [23][25] and is connected to the auditory pathway directly as well as indirectly [26][29].…”
Section: Introductionmentioning
confidence: 98%
“…The incubating conditions as standardized by Kauser et al() were followed. Briefly, eggs were incubated at 36°C ± 1°C temperature and 60–70% relative humidity.…”
Section: Methodsmentioning
confidence: 99%
“…In chicks, exposure to prenatal auditory stimuli (from E 10) results in an early functional maturation of the auditory system (Wadhwa et al, ; Alladi et al, , ,; Jain et al, ). There is also enhancement of the neural substrate in the mediorostral neostriatum/ hyperstriatum ventrale (MNH, Panicker et al, ) and in the hippocampus (Chaudhury et al, ), facilitation of spatial orientation (Chaudhury et al, ) and learning abilities of the neonatal chicks (Kauser et al, ); suggesting thereby that any specific prenatal sensory stimulus can affect the development of other neural areas that are associated to it or involved in the processing of that particular stimulus (Lickliter, ). In birds, different sensory systems become functional in a stereotypic order, i.e.…”
Section: Introductionmentioning
confidence: 99%
“…Music is a noninvasive, culturally acceptable intervention with multiple putative direct and indirect beneficial effects on mother and foetus through the pregnancy and perinatal period. In animals, prenatal music exposure has been shown to improve postnatal spatial learning and memory; to reduce isolation stress [4]. Music has been found to beneficially affect stress response and recovery from critical illness or surgery [5, 6].…”
Section: Introductionmentioning
confidence: 99%